2000
DOI: 10.1021/ma9910639
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Alignment of ABC Block Copolymer Microdomains via Solvent Vapor Treatment

Abstract: We have studied the microdomain morphology of thin ABC triblock copolymer films supported by a solid substrate. The films were exposed to various solvent vapors, and the effect of the solvent removal speed on the resulting morphologies is investigated. Slow solvent extraction rates lead to a parallel alignment of lamellar microphases within the plane of the film. On fast drying, a perpendicular orientation of the lamellae is found. In the case of block copolymer samples with a highly anisotropic macroscopic sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
242
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(253 citation statements)
references
References 21 publications
10
242
0
Order By: Relevance
“…Although, thermal annealing has been shown to work well for a range of polymer films, the temperature window between the T g and the order-disorder transition temperature (ODT) for some polymer films is too narrow to achieve thermodynamic equilibrium [45]. A technique known as solvent annealing or swelling, first demonstrated by Kim et al [39] with polystyrene-polybutadiene-polystyrene (SBS) triblock copolymer, has received considerable attention over the last decade as an alternative to thermal annealing as it can not only induce microphase separation (orientation ordering) but also improve translational ordering [46].…”
Section: Block Copolymer (Bcp) Thin Filmsmentioning
confidence: 99%
“…Although, thermal annealing has been shown to work well for a range of polymer films, the temperature window between the T g and the order-disorder transition temperature (ODT) for some polymer films is too narrow to achieve thermodynamic equilibrium [45]. A technique known as solvent annealing or swelling, first demonstrated by Kim et al [39] with polystyrene-polybutadiene-polystyrene (SBS) triblock copolymer, has received considerable attention over the last decade as an alternative to thermal annealing as it can not only induce microphase separation (orientation ordering) but also improve translational ordering [46].…”
Section: Block Copolymer (Bcp) Thin Filmsmentioning
confidence: 99%
“…[116][117][118] Rehse et al demonstrated for the first time the presence of non-bulk surface-reconstruction morphologies using polystyrene-block-polybutadiene-blockpoly-(methyl methacrylate) (SBM), polybutadiene-block-polystyrene-block-poly(methyl methacrylate) (BSM) and polystyrene-block-polybutadiene-block-poly(tert-butyl methacrylate) (SBT), 119 and Ludwigs et al systematically studied the phase behavior of SVT thin films and could match these results to simulations based on self-consistent field (SCF) theory.…”
Section: Abc Triblock Copolymersmentioning
confidence: 99%
“…31 Among the strategies to induce ordering, directional solvent evaporation is very promising for submicron lithography due to its simplicity and low processing costs. 18,[32][33][34][35][36] In principle, the rate of evaporation and evaporation-induced solvent flow can be manipulated to guide the orientated growth and positioning of microdomains. Evaporation results in a solvent concentration gradient, which induces the ordering that starts from the surface and propagates toward the interior and eventually throughout the entire film.…”
Section: Introductionmentioning
confidence: 99%